Three-Dimensional Mapping of Chorioretinal Vascular Oxygen Tension in the Rat - Shahidi, Mahnaz (2008)
PURPOSE: An optical section phosphorescence lifetime imaging system was developed for three-dimensional mapping of oxygen tension (PO(2)) in chorioretinal vasculatures. METHODS: A laser line was projected at an oblique angle and scanned on the retina after intravenous injection of an oxygen-sensitive molecular probe to generate phosphorescence optical section images. An automated software algorithm segmented and combined images from spatially adjacent locations to construct depth-displaced en face retinal images. Intravascular PO(2) was measured by determining the phosphorescence lifetime. Three-dimensional chorioretinal PO(2) maps were generated in rat eyes under varying fractions of inspired oxygen. RESULTS: Under an air-breathing condition, mean PO(2) in the choroid, retinal arteries, capillaries, and veins were 58 ± 2 mm Hg, 47 ± 2 mm Hg, 44 ± 2 mm Hg, and 35 ± 2 mm Hg, respectively. The mean arteriovenous PO(2) difference was 12 ± 2 mm Hg. With a lower fraction of inspired oxygen, chorioretinal vascular PO(2) and mean arteriovenous PO(2) differences decreased compared with measurements under an air-breathing condition. Retinal venous PO(2) was statistically lower than PO(2) measured in the retinal artery, capillaries, and choroid (P < 0.004). CONCLUSIONS: Three-dimensional mapping of chorioretinal oxygen tension allowed quantitative PO(2) measurements in large retinal blood vessels and in retinal capillaries. This method has the potential to facilitate better understanding of retinal oxygenation in health and disease.